Social media usage as health communication platform by adolescents with acne in Indonesia - Fawzian, Rheivita Mutiara; Mulyana, Slamet; Trulline, Putri (Faculty of Communication Sciences Universitas Padjadjaran, 2023)
Social media has become a platform often used for health communication in Indonesia. The age group that uses it the most is adolescents who at that age are having acne problems. It has led to the emergence of the phenomenon of increasing health communication about acne on social media, from the need for curing information to psychological support. However, not all social media can be used by adolescents with acne to get the right health communication. Therefore, this research will examine the use of social media in conducting effective health communication by adolescents with acne using the theory of Computer-Mediated Communication along with health communication scope. This study aimed to determine the choice of social media use and the forms of health communication activities conducted by adolescents with acne on social media. The method used is descriptive qualitative, by conducting interviews with adolescents with acne in Indonesia. The results of this study are that there are six social media used by adolescents with acne. Instagram is mainly used as well as considered the most effective. The scope of health communication is around information related to healing, support and motivation, and health promotion by interacting interpersonally and uploading content to a broad audience. These findings can be a consideration for adolescents with acne and the general public using social media based on the intended use and characteristics. Several aspects that are considered will affect the information obtained.